(3LGeY GdeTcdGJs - (3eLghds ((3eMeO jMji GdeVaQj GdfLajs)
(3ChdgG (B:s
(3HSe Gddg (B.. (3bGd eMeO gh GHf eGdc (B...(3cdGefG Cj eYGTQ GdfMhjjf YHGQI Yf daX eajO JGeI jUM GdGcJaGA dg cdG GdaGFOI aj GSJbe Hbhdg daX GOMd cd daX hHbhdg eajO CNQL Gdeged hCONd GdeSJYed Hbhd GdeUfa (B...s
(3BNQgG (B:s
.. (3CYfj GddaX GdeSJYed aj ZjQ eG hVY dg haj GdGUWdGM Hd GdeQGO efg GdeLGR GdYbdj GdeSei HGdeLGR aj GdESfGO hgh GSfGO GdTjA ef gh dg bhdg (B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdfMhs